Organic cation‐supported layered vanadate cathode for high‐performance aqueous zinc‐ion batteries - Changding Wang; Yingfang Li; Sida Zhang; Tian‐Yi Sang; Yu Lei; Ruiqi Liu; Fu Wan; Yuejiao Chen; Weigen Chen; Yujie Zheng; Shuhui Sun (Carbon Energy)
Abstract Layered vanadates are ideal energy storage materials due to their multielectron redox reactions and excellent cation storage capacity. However, their practical application still faces challenges, such as slow reaction kinetics and poor structural stability. In this study, we synthesized [Me2NH2]V3O7 (MNVO), a layered vanadate with expended layer spacing and enhanced pH resistance, using a one‐step simple hydrothermal gram‐scale method. Experimental analyses and density functional theory (DFT) calculations revealed supportive ionic and hydrogen bonding interactions between the thin‐layered [Me2NH2]+ cation and [V3O7]− anion layers, clarifying the energy storage mechanism of the H+/Zn2+ co‐insertion. The synergistic effect of these bonds and oxygen vacancies increased the electronic conductivity and significantly reduced the diffusion energy barrier of the insertion ions, thereby improving the rate capability of the material. In an acidic electrolyte, aqueous zinc‐ion batteries employing MNVO as the cathode exhibited a high specific capacity of 433 mAh g−1 at 0.1 A g−1. The prepared electrodes exhibited a maximum specific capacity of 237 mAh g−1 at 5 A g−1 and maintained a capacity retention of 83.5% after 10,000 cycles. This work introduces a novel approach for advancing layered cathodes, paving the way for their practical application in energy storage devices.